Agronomic and economic evaluation of ratoon rice cropping systems with perennial rice varieties in West Africa - Dossou-Yovo, Elliott Ronald; Ibrahim, A.; Akpoffo, Marius A.Y.; Belko, N.; Ndindeng, S.A.; Saito, K.; Futakuchi, K. (Elsevier, 2024)
Context: With rapid population increase, labour scarcity, and soil nutrient depletion, agricultural lands must be used sustainably to meet the ever-increasing demands for food and livelihood. Perennial rice varieties show promise in meeting the conflicting needs for reducing input use while increasing agricultural production. But, little is known about their agronomic and economic performances and the suitable cropping system in West Africa. Objective: The objective of this study was to evaluate the effects of the cropping system and perennial rice variety on grain yield, labour productivity, and profitability in irrigated lowlands in West Africa. Methods: Experiments were conducted over two years at two sites: Mbe in Cote ˆ d′Ivoire and Ndiaye in Senegal located in the sub-humid and Sahelian climatic zones, respectively. The treatments consisted of three cropping systems [one transplanting and two ratoons per year (rice–ratoon–ratoon), one transplanting and all other ratoons (rice–ratoon continuous), and transplanting twice a year (rice–rice)], and six varieties (five perennial rice varieties: PR101, PR107, PR23, PR24, and PR25 and a local check variety, which was WITA9 and Sahel108 in Mbe and Ndiaye, respectively. Results: There were significant effects of the cropping system and variety, and their interaction on grain yield, labour productivity, and profitability at both sites. In the rice–ratoon–ratoon system, the cumulative grain yield over two years of PR23 and PR25 at Mbe (28.8 t/ha) and PR107 at Ndiaye (22.1 t/ha) was similar to that of the local check in the rice–rice system. The average cumulative grain yield across varieties over two years was the lowest in rice–ratoon continuous system at both sites. Grain yield declined with an increased number of ratoon cropping seasons in the rice–ratoon continuous system. Crop duration and the percentage of regrowth rates (ratio of the number of panicles of the ratoon crop to the number of panicles of the main crop in percentage) were the main drivers of grain yield in the ratoon cropping seasons. At Mbe, the highest labour productivity (39.6 – 39.9 kg/day) and profit (5814 – 5844 USD/ha) were achieved with PR23 and PR25 in the rice–ratoon–ratoon system, while at Ndiaye, the highest labour productivity (24.3 kg/day) and profit (2689 USD/ha) were achieved with PR107 in the rice–ratoon–ratoon system, as they had lower labour input and production costs than those in the rice–rice system with the local check. Conclusions: Grain yield could not be sustained in two years of the continuous ratoon cropping system with perennial rice. The rice–ratoon–ratoon system with PR23 and PR25 at Mbe and PR107 at Ndiaye offers alternative options to the conventional rice–rice system for increasing labour productivity and profitability but may require more water due to the longer crop duration. Implications: Realizing the full potential of perennial rice requires the identification of the causes of rapid yield decline and the development of agronomic practices for enhancing grain yield under ratoon cropping systems in West Africa.